2010
DOI: 10.1186/1749-7922-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Encountering Meckel's diverticulum in emergency surgery for ascaridial intestinal obstruction

Abstract: BackgroundMeckel's diverticulum is the most common congenital anomaly of the gastrointestinal tract. In children with intestinal ascariasis, the diverticulum remains asymptomatic or rarely the Ascaris lumbricoides may lead to its complications in the presence of massive intestinal roundworm load. Given that preoperative diagnosis is seldom carried out, when Meckel's diverticulum is found at laparotomy for obstructive intestinal complications of roundworm, the diverticulum should be removed as complications may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Added together, obstruction, hemorrhage, and inflammation account for 69.5% to 100% of symptomatic patients in each of the largest retrospective patient series. Rarer forms of symptomatic Meckel's, including umbilical abnormalities involving the vitelline duct, [39] parasite-infections involving the Meckel's, [42] Meckelian cancers, [43] as well as uncertain cases, [28] account for the remainder.…”
Section: Resultsmentioning
confidence: 99%
“…Added together, obstruction, hemorrhage, and inflammation account for 69.5% to 100% of symptomatic patients in each of the largest retrospective patient series. Rarer forms of symptomatic Meckel's, including umbilical abnormalities involving the vitelline duct, [39] parasite-infections involving the Meckel's, [42] Meckelian cancers, [43] as well as uncertain cases, [28] account for the remainder.…”
Section: Resultsmentioning
confidence: 99%
“…Meckel's diverticulum is symptomatic in 4–6% of the patients [ 5 , 6 ]. The ratio of men to women in symptomatic cases is reported to be 3/1 [ 2 , 7 ]. Most common complications include ulceration, intestinal obstruction, hemorrhage, perforation, intussusception, vesicodiverticular fistula, and malignancy [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Louw 23 , in a review, found intestinal obstruction, biliary tract diseases, pancreatic diseases, peritonitis and appendicitis due to roundworms. Mishra PK et al 24 and Wani I et al 25 in their respective studies also found the similar abdominal complications and even the involvement of meckle's diverticulam. In the present study we observed near to same set of abdominal complications.…”
Section: Discussionmentioning
confidence: 60%